2017
DOI: 10.1292/jvms.17-0196
|View full text |Cite
|
Sign up to set email alerts
|

Rapid exacerbation of renal function after administration of hydroxyethyl starch in a dog

Abstract: Hydroxyethyl starches (HES) are commonly used synthetic colloidal solution in veterinary medicine. Despite of possible adverse effect to kidney injury in human, there is no report about nephrotoxic effects of HES in dogs. HES was administered to a Golden retriever (4-year-old, intact male) with ascites in order to increase plasma osmolality. Initially, the dog was mild azotemic, however, kidney function was rapidly deteriorated after several days of HES administration. Finally, histopathological examination re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The observed transient proteinuria and azotaemia could be the result of damage caused by flurbiprofen, with AKI being the most frequent consequence of NSAID overdose. As reported elsewhere, high‐dose hydroxyethyl starch administration may have also contributed to this dog's acute kidney injury 18,19 . Despite reports of using half HES and half plasma as replacement, 20,21 recent debates and controversies surrounding colloid use make the authors recommend caution when using high‐dose colloids.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The observed transient proteinuria and azotaemia could be the result of damage caused by flurbiprofen, with AKI being the most frequent consequence of NSAID overdose. As reported elsewhere, high‐dose hydroxyethyl starch administration may have also contributed to this dog's acute kidney injury 18,19 . Despite reports of using half HES and half plasma as replacement, 20,21 recent debates and controversies surrounding colloid use make the authors recommend caution when using high‐dose colloids.…”
Section: Discussionmentioning
confidence: 81%
“…As reported elsewhere, high-dose hydroxyethyl starch administration may have also contributed to this dog's acute kidney injury. 18,19 Despite reports of using half HES and half plasma as replacement, 20,21 recent debates and controversies surrounding colloid use make the authors recommend caution when using high-dose colloids. Based on current recommendations as well as the authors' experience, the colloid dose described in this case report should not be used as reference and a more conservative volume should be considered instead.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a retrospective cohort study comparing dogs treated with either a tetrastarch or crystalloids found no difference between the incidence of acute kidney injury or serum creatinine between groups (Sigrist, Kälin & Dreyfus 2017). However, Bae et al (2017) published a case report wherein they describe the development of acute kidney injury in a dog after administration of a tetrastarch (HES 6% 130/0.4), although the animal in question already had underlying renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular lysosomes do not have the ability to degrade HES, thus the molecules remain within these cells potentially adversely affecting them. Over the last decade, the use of HES in critically ill human patients has been associated with increased risk of acute kidney injury, increased rates of renal replacement therapy and hepatopathy, amongst others (Bae et al 2017). Similarly, the use of pentastarch (10% HES 250/0.5/5:1) was associated with an increased incidence of acute kidney injury in dogs.…”
Section: Introductionmentioning
confidence: 99%